Nigeria and the political economy of development : the dreams, the myth, and the reality - Ajayi, Simeon Ibidayo; Nigerian Economic Society (Ibadan, Nigeria : Nigerian Economic Society, Secretariat, Department of Economics, University of Ibadan, 2003)
A Presidential address to the 44th Annual Conference of the Nigerian Economic Society, held at the University of Ibadan Conference Centre, Ibadan, 27-29 August 2003.
"Presidential address to the 44th Annual Conference of the Nigerian Economic Society, held at the University of Ibadan Conference Centre, Ibadan, 27-29 August 2003."
Includes bibliographical references (p. 27-28).
oif 18/07/2018
Loans
Keywords: Economic history; Economic policy; Intergovernmental fiscal relations; Nigeria